Farnesyltransferase inhibitors as radiation sensitizers. - Mckenna, W; Muschel, R; Gupta, A; Hahn, S; Bernhard, E (2002)
Activation of Ras, by mutation, overexpression, or by signaling through tyrosine kinase receptors, is associated with radioresistance. Thus, therapies that inhibit Ras function could be an effective means to radiosensitize selected types of solid tumors. Inhibition of Ras prenylation using a variety of farnesyltransferase inhibitors resulted in radiosensitization of tumor cells that expressed activated Ras, both in vitro and in xenograft models. Farnesyltransferase inhibitor treatment could also inhibit tumor regrowth following irradiation of mice bearing T24 tumor xenografts that express activated Ras. In a phase I trial of the farnesyltransferase inhibitor L-778-123 and radiotherapy in patients with locally advanced head and neck cancer and non-small cell lung cancer, a high response rate was observed coupled with a mild toxicity profile. Additional clinical trials should shed light on the potential of this and other farnesyltransferase inhibitors to serve as radiosensitizers and may identify molecular markers that could predict a response to these agents.